Incidence and Outcomes of Pulmonary Hypertension in Preterm Infants with Bronchopulmonary Dysplasia: Systematic Review and Meta-Analysis. (1st June 2016) - Al-ghanem, G; Thomas, S; Helou, S el; Fusch, C; Mukerji, A
Abstract: BACKGROUND: Bronchopulmonary dysplasia (BPD) remains the most common complication of prematurity and is associated with pulmonary hypertension (PH). The incidence of PH in BPD and its clinical impact, as compared to BPD without PH, remains unclear due to variability in the reported literature. OBJECTIVES: To determine the incidence of PH in BPD and evaluate short term outcomes in BPD with PH compared to BPD without PH. DESIGN/METHODS: A systematic review of the literature was conducted using pre-specified search terms in MEDLINE from January 2000 through August 2015. Risk of bias of included studies was performed using a modified Newcastle-Ottawa scale. Meta-analyses for pre-specified outcomes were performed with RevMan 5.3 when appropriate using a random-effects model and odds ratios (ORs) and mean differences (MDs) were pooled. RESULTS: Of 13 studies included, majority (12) had a low-moderate risk of bias. The mean (SD) incidence of PH was 18 (7) % in all forms of BPD (9 studies) and 26 (11) % when limited to moderate-severe BPD (4 studies). The odds ratio of PH in all forms of BPD was 3.43 (95% CI 1.55, 7.58) compared to no BPD (Figure). Pooled results from meta-analyses of short term outcomes in BPD patients with PH versus BPD patients without PH are shown in Table. Clinical predictors of PH in BPD after adjusted analyses (4 studies) were low birth weight, small for gestational age, postnatal infection, oligohydramnios, and APGAR score ≤ 6. CONCLUSION: There is a significant risk of PH in patients with BPD. Routine screening for PH among BPD patients should be considered in light of poorer short term outcomes in BPD patients with PH as compared with BPD patients without PH.